2022
DOI: 10.3390/genes13091657
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations for Interpreting and Reporting Silent Carrier and Disease-Modifying Variants in SMA Testing Workflows

Abstract: Genetic testing for SMA diagnosis, newborn screening, and carrier screening has become a significant public health interest worldwide, driven largely by the development of novel and effective molecular therapies for the treatment of spinal muscular atrophy (SMA) and the corresponding updates to testing guidelines. Concurrently, understanding of the underlying genetics of SMA and their correlation with a broad range of phenotypes and risk factors has also advanced, particularly with respect to variants that mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 41 publications
0
5
0
1
Order By: Relevance
“…Így ők fenotípusosan nem feltűnőek, és rutin szűrő genetikai teszttel sem azonosíthatók, úgy nevezett "csendes hordozók" 5 . Az SMN1 pontmutációit hordozó egyének is csendes hordozók, mivel rutin szűrő vizsgálatokon ők sem kerülnek detektálásra 5 .…”
Section: Q Spinalis Izomatrophia (Gerincvelői Izomsorvadás)unclassified
“…Így ők fenotípusosan nem feltűnőek, és rutin szűrő genetikai teszttel sem azonosíthatók, úgy nevezett "csendes hordozók" 5 . Az SMN1 pontmutációit hordozó egyének is csendes hordozók, mivel rutin szűrő vizsgálatokon ők sem kerülnek detektálásra 5 .…”
Section: Q Spinalis Izomatrophia (Gerincvelői Izomsorvadás)unclassified
“…A large-scale study found that carriers of SMN1 gene deletion have a frequency of 1/54 in the population, with an incidence rate of 1/11,000. [2][3][4] Based on the age of onset and the timing of milestone motor events, five types (0 to IV) have been established. Prenatal onset type 0 and infantile onset type I are the most severe and associated with increased mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Of patients with SMA type 3, 64% have three copies of SMN2 and 31% have four copies of SMN2 [12]. Mutations in SMN2 also modify the severity of SMA [13]. The most common is the c.859G > C variant, which promotes exon 7 inclusion, increasing the amount of correct SMN protein produced [13,14].…”
Section: Introductionmentioning
confidence: 99%